Human Platelet Polymorphism can be a genetic marker associated with HIV/HCV coinfection - Grotto, Rejane Maria Tommasini [UNESP]; Picelli, Natália [UNESP]; Souza, Lenice do Rosário de[UNESP]; Silva, Giovanni Faria [UNESP]; Ferrasi, Adriana Camargo [UNESP]; Silveira, Liciana Vaz de Arruda [UNESP]; Pardini, Maria Inês de Moura Campos [UNESP] (Wiley-Blackwell, 2015)
To evaluate the associations of HPA polymorphisms -1, -3, and -5 with HIV/HCV coinfection were included in this study 60 HIV/HCV-coinfected patients from the Sao Paulo State health service centers. Data reported by Verdichio-Moraes et al. (2009: J. Med Virol 81:757-759) were used as the non-infected and HCV monoinfected groups. Human Platelet Polymorphism genotyping was performed in 60 Patients co-infected with HIV/HCV by PCR-SSP or PCR-RFLP. HIV subtyping and HCV genotyping was performed by RT-PCR followed sequencing. The data analyses were performed using the χ2 test or Fisher's Exact Test and the logistic regression model. Patients coinfected with HIV/HCV presented HCV either genotype 1 (78.3%) or non-1 (21.7%) and HIV either subtype B (85.0%) or non-B (15%). The Human Platelet Polymorphism-1a/1b genotype was more frequent (P < 0.05) in HIV/HCV coinfection than in HCV monoinfection and the allelic frequency of Human Platelet Polymorphism-5b in the Patients coinfected with HIV/HCV was higher (P < 0.05) than in HCV monoinfected cases and non-infected individuals. These data suggest that the presence of specific HPA allele on platelets could favor the existence of coinfection. On the other hand, Human Platelet Polymorphism-5a/5b was more frequent (P < 0.05) in HIV/HCV coinfected and HCV monoinfected groups than in the non-infected individuals, suggesting that this platelet genotype is related to HCV infection, regardless of HIV presence. Results suggest that the Human Platelet Polymorphism profile in HIV/HCV coinfected individuals differs from the one of both HCV monoinfected and non-infected population. So, the Human Platelet Polymorphism can be a genetic marker associated with HIV/HCV coinfection.
Keywords: HIV/HVC coinfection; Human platelet polymorphism -1; Human platelet polymorphism -3; Human platelet polymorphism -5; Polymorphism